An Intelligent Architecture for Recruitment Process Using Machine Learning - Joy, Jiso K; Sreedev , SB; Vishnu , AK; Rejimoan, R (International Journal of Computer Sciences and Engineering, 2019)
Recruitment process has become one of the laying foundations for the development of an organization. All organizations are looking for the perfect candidate to build their enterprises. Finding the right candidate for the right job is becoming more and more difficult. Recruiter and other HR professionals that don`t use innovative recruiting strategies are often unable to find job candidates that are suitable for the job. To find the right candidates, recruiters have to have a well-planned and developed recruiting and hiring strategies. Machine learning is emerging as a strategy to help employers more efficiently conduct talent sourcing and recruitment. Traditional recruiting process requires lot of time and effort along with various costs that comes with it for filtering out the candidate. This paper will propose an automated interview system which uses machine learning to gauge the candidates based on the emotions expressed in the interview process and thus find the right person for the right job.